The Reliability Analysis for Information Security Metrics in Academic Environment - Ibnugraha, Prajna Deshanta; Satria, Anas; Nagari, Fabian Sekar; Rizal, Moch Fahru; NonAlinsavath, Khamla NonAlinsavath (JOIV : International Journal on Informatics Visualization, 2023)
Today, academic institution involves digital data to support the educational process. It has advantages, especially related to ease of access and process. However, security problems appear related to digital data. There were several information security incidents in the academic environment. In order to mitigate the problem, metrics identification is required to determine the risk of incidents. There are many risks model and metrics to estimate the risk, such as DREAD, OWASP, CVSS, etc. However, specific metrics are required to obtain appropriate risk values. Therefore, this study aims to define metrics for an academic institution. The proposed metrics are obtained from The Family Educational Rights and Privacy Act (FERPA) regulation. It consists of directory information, educational information, personally identifiable information, and risk of information leakage. In order to achieve the objective, this study involves survey and reliability analysis to result in output. The survey is conducted by involving 90 respondents with various levels of education and jobs. The Cronbach's alpha and Test-retest are methods to determine this study's reliability. According to reliability analysis, the Cronbach's alpha method results in coefficients for the metrics between 0.730 - 0.911, while the Test-retest method results in coefficients between 0.630 - 0.797. These coefficients have a reliable category, so the proposed metrics are adequate for determining risk of information security incidents in academic environments. The reliable metrics will be developed as variables of the risk assessment model for the academic environment in the future study.Â